(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY The purpose of this study was to evaluate the safety and efficacy of endovenous laser ablation (EVLA) in patients 75 years and older in an outpatient setting. METHODS In this multicentre retrospective study, we collected the demographic, procedural and outcome data of all consecutive patients with varicose veins class C2 to C6 undergoing EVLA of truncal and accessory saphenous veins. The primary efficacy endpoint was complete ablation of the treated veins diagnosed with duplex ultrasound at 4-week follow up. The primary safety endpoint was endothermal heat-induced thrombosis (EHIT) and deep vein thrombosis (DVT) at 4-week follow up as diagnosed by duplex ultrasound. A secondary endpoint was minor or major bleeding. RESULTS Between February 2009 and December 2015, a total of 829 patients were treated with EVLA of the truncal and accessory saphenous veins. Among them, 747 were <75 years old (group 1) and 82 were ≥75 years old (group 2). The primary efficacy outcome was reached in 739 patients (98.9%) in group 1 and in 80 patients (97.6%) in group 2 (odd ratio [OR] 0.43, confidence interval [CI] 0.09–2.07; p = 0.295). The number of patients with EHIT type 2 and DVT were 4 (0.5%) and 2 (0.3%), respectively, in group 1, and 2 (2.4%) and 1 (1.2%), respectively, in group 2 (OR 4.64, CI 0.83–25.75; p = 0.079 and OR 4.59, CI 0.41–51.27; p = 0.215, respectively). Minor bleeding events occurred in 36 patients (4.8%) in group 1 and 7 patients (8.9%) in group 2 (OR 1.84, CI 0.79-4.29; p = 0.155). No major bleeding occurred in either group. Propensity score-matched analysis revealed no significant difference in efficacy and safety outcomes. CONCLUSION EVLA performed as an outpatient procedure seems to be effective and safe in the elderly population as compared to the younger age group.